7
$\begingroup$

How to show that $$\sum_{n=1}^\infty\frac{1}{n^2+3n+1}=\frac{\pi\sqrt{5}}{5}\tan\frac{\pi\sqrt{5}}{2}$$ ?

My try:

We have $$n+3n+1=\left(n+\frac{3+\sqrt{5}}{2}\right)\left(n+\frac{3-\sqrt{5}}{2}\right),$$ so $$\frac{1}{n^2+3n+1}=\frac{2}{\sqrt{5}}\left(\frac{1}{2n+3-\sqrt{5}}-\frac{1}{2n+3+\sqrt{5}}\right).$$ Then, I don't know how to proceed.

$\endgroup$
3
  • $\begingroup$ What makes you the greatest difficulty in this task? Which way went your transformations? $\endgroup$ – Tacet Dec 5 '14 at 23:51
  • $\begingroup$ This answer should be useful: math.stackexchange.com/questions/112161 . $\endgroup$ – anomaly Dec 6 '14 at 0:11
  • $\begingroup$ Duplicate of this. $\endgroup$ – Lucian Dec 6 '14 at 3:11
8
$\begingroup$

I think we can make some use of the residue theorem. Write $n^2+3 n+1 = (n+3/2)^2-5/4$ and the sum is

$$\sum_{n=1}^{\infty} \frac1{\left (n+\frac{3}{2} \right )^2-\frac{5}{4}} = \frac12 \sum_{n=-\infty}^{\infty} \frac1{\left (n+\frac{3}{2} \right )^2-\frac{5}{4}} - 1 +1$$

(To get the doubly infinite sum, I had to add back the $n=0$ and $n=-1$ terms, which happen to sum to zero.)

The sum on the RHS may be attacked via the residue theorem, using the following:

$$\sum_{n=-\infty}^{\infty} f(n) = - \pi \sum_k \operatorname*{Res}_{z=z_k} [f(z)\cot{\pi z} ] $$

where $z_k$ is a non-integer pole of $f$. The poles are at

$$z_{\pm} = -\frac{3}{2} \pm \frac{\sqrt{5}}{2} $$

The sum is then equal to

$$\frac{\pi}{2 \sqrt{5}} \left [\cot{\left (\frac{3 \pi}{2} - \frac{\sqrt{5} \pi}{2} \right )} - \cot{\left (\frac{3 \pi}{2} + \frac{\sqrt{5} \pi}{2} \right )} \right ] = \frac{\pi}{\sqrt{5}}\tan{\frac{\sqrt{5}\pi}{2}}$$

$\endgroup$
1
$\begingroup$

Note $$ n^2+3n+1=(n+\frac{3}{2})^2+\left(\frac{\sqrt 5i}{2}\right)^2 $$ and and hence \begin{eqnarray} \sum_{n=0}^\infty\frac{1}{n^2+3n+1}&=&\sum_{n=0}^\infty\frac1{(n+\frac{3}{2})^2+\left(\frac{\sqrt 5i}{2}\right)^2}\\ &=&\frac12\sum_{n=-\infty}^\infty\frac1{(n+\frac{3}{2})^2+\left(\frac{\sqrt 5i}{2}\right)^2}. \end{eqnarray} Then using the result from this, you will get the answer.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.